New Australian guidelines for the treatment of alcohol problems: an overview of recommendations. Issue Volume 215:Issue S7(2021)Supplement (3rd October 2021) - Haber, Paul S; Riordan, Benjamin C; Winter, Daniel T; Barrett, Liz; Saunders, John; Hides, Leanne; Gullo, Matthew; Manning, Victoria; Day, Carolyn A; Bonomo, Yvonne; Burns, Lucinda; Assan, Robert; et al.
Abstract : Summary of recommendations and levels of evidence: Chapter 2: Screening and assessment for unhealthy alcohol use: Screening Screening for unhealthy alcohol use and appropriate interventions should be implemented in general practice (Level A), hospitals (Level B), emergency departments and community health and welfare settings (Level C). Quantity–frequency measures can detect consumption that exceeds levels in the current Australian guidelines (Level B). The Alcohol Use Disorders Identification Test (AUDIT) is the most effective screening tool and is recommended for use in primary care and hospital settings. For screening in the general community, the AUDIT‐C is a suitable alternative (Level A). Indirect biological markers should be used as an adjunct to screening (Level A), and direct measures of alcohol in breath and/or blood can be useful markers of recent use (Level B). Assessment Assessment should include evaluation of alcohol use and its effects, physical examination, clinical investigations and collateral history taking (Level C). Assessment for alcohol‐related physical problems, mental health problems and social support should be undertaken routinely (GPP). Where there are concerns regarding the safety of the patient or others, specialist consultation is recommended (Level C). Assessment should lead to a clear, mutually acceptable treatment plan which specifies interventions to meet the patient's needs (Level D). Sustained abstinence is the optimal outcome for most patients with alcohol dependence (Level C). Chapter 3: Caring for and managing patients with alcohol problems: interventions, treatments, relapse prevention, aftercare, and long term follow‐up: Brief interventions Brief motivational interviewing interventions are more effective than no treatment for people who consume alcohol at risky levels (Level A). Their effectiveness compared with standard care or alternative psychosocial interventions varies by treatment setting. They are most effective in primary care settings (Level A). Psychosocial interventions Cognitive behaviour therapy should be a first‐line psychosocial intervention for alcohol dependence. Its clinical benefit is enhanced when it is combined with pharmacotherapy for alcohol dependence or an additional psychosocial intervention (eg, motivational interviewing) (Level A). Motivational interviewing is effective in the short term and in patients with less severe alcohol dependence (Level A). Residential rehabilitation may be of benefit to patients who have moderate‐to‐severe alcohol dependence and require a structured residential treatment setting (Level D). Alcohol withdrawal management Most cases of withdrawal can be managed in an ambulatory setting with appropriate support (Level B). Tapering diazepam regimens (Level A) with daily staged supply from a pharmacy or clinic are recommended (GPP). Pharmacotherapies for alcohol dependence Acamprosate is recommended to help maintain abstinence from alcohol (Level A). Naltrexone is recommended for prevention of relapse to heavy drinking (Level A). Disulfiram is only recommended in close supervision settings where patients are motivated for abstinence (Level A). Some evidence for off‐label therapies baclofen and topiramate exists, but their side effect profiles are complex and neither should be a first‐line medication (Level B). Peer support programs Peer‐led support programs such as Alcoholics Anonymous and SMART Recovery are effective at maintaining abstinence or reductions in drinking (Level A). Relapse prevention, aftercare and long‐term follow‐up Return to problematic drinking is common and aftercare should focus on addressing factors that contribute to relapse (GPP). A harm‐minimisation approach should be considered for patients who are unable to reduce their drinking (GPP). Chapter 4: Providing appropriate treatment and care to people with alcohol problems: a summary for key specific populations: Gender‐specific issues Screen women and men for domestic abuse (Level C). Consider child protection assessments for caregivers with alcohol use disorder (GPP). Explore contraceptive options with women of reproductive age who regularly consume alcohol (Level B). Pregnant and breastfeeding women Advise pregnant and breastfeeding women that there is no safe level of alcohol consumption (Level B). Pregnant women who are alcohol dependent should be admitted to hospital for treatment in an appropriate maternity unit that has an addiction specialist (GPP). Young people Perform a comprehensive HEEADSSS assessment for young people with alcohol problems (Level B). Treatment should focus on tangible benefits of reducing drinking through psychotherapy and engagement of family and peer networks (Level B). Aboriginal and Torres Strait Islander peoples Collaborate with Aboriginal or Torres Strait Islander health workers, organisations and communities, and seek guidance on patient engagement approaches (GPP). Use validated screening tools and consider integrated mainstream and Aboriginal or Torres Strait Islander‐specific approaches to care (Level B). Culturally and linguistically diverse groups Use an appropriate method, such as the "teach‐back" technique, to assess the need for language and health literacy support (Level C). Engage with culture‐specific agencies as this can improve treatment access and success (Level C). Sexually diverse and gender diverse populations Be mindful that sexually diverse and gender diverse populations experience lower levels of satisfaction, connection and treatment completion (Level C). Seek to incorporate LGBTQ‐specific treatment and agencies (Level C). Older people All new patients aged over 50 years should be screened for harmful alcohol use (Level D). Consider alcohol as a possible cause for older patients presenting with unexplained physical or psychological symptoms (Level D). Consider shorter acting benzodiazepines for withdrawal management (Level D). Cognitive impairment Cognitive impairment may impair engagement with treatment (Level A). Perform cognitive screening for patients who have alcohol problems and refer them for neuropsychological assessment if significant impairment is suspected (Level A). Summary of key recommendations and levels of evidence: Chapter 5: Understanding and managing comorbidities for people with alcohol problems: polydrug use and dependence, co‐occurring mental disorders, and physical comorbidities: Polydrug use and dependence Active alcohol use disorder, including dependence, significantly increases the risk of overdose associated with the administration of opioid drugs. Specialist advice is recommended before treatment of people dependent on both alcohol and opioid drugs (GPP). Older patients requiring management of alcohol withdrawal should have their use of pharmaceutical medications reviewed, given the prevalence of polypharmacy in this age group (GPP). Smoking cessation can be undertaken in patients with alcohol dependence and/or polydrug use problems; some evidence suggests varenicline may help support reduction of both tobacco and alcohol consumption (Level C). Co‐occurring mental disorders More intensive interventions are needed for people with comorbid conditions, as this population tends to have more severe problems and carries a worse prognosis than those with single pathology (GPP). The Kessler Psychological Distress Scale (K10 or K6) is recommended for screening for comorbid mental disorders in people presenting for alcohol use disorders (Level A). People with alcohol use disorder and comorbid mental disorders should be offered treatment for both disorders; care should be taken to coordinate intervention (Level C). Physical comorbidities Patients should be advised that alcohol use has no beneficial health effects. There is no clear risk‐free threshold for alcohol intake. The safe dose for alcohol intake is dependent on many factors such as underlying liver disease, comorbidities, age and sex (Level A). In patients with alcohol use disorder, early recognition of the risk for liver cirrhosis is critical. Patients with cirrhosis should abstain from alcohol and should be offered referral to a hepatologist for liver disease management and to an addiction physician for management of alcohol use disorder (Level A). Alcohol abstinence reduces the risk of cancer and improves outcomes after a diagnosis of cancer (Level A).